Odontogenic Myxoma: Systematic review and bias analysis - Dotta, Jéssica Helena [UNESP]; Miotto, Larissa Natiele [UNESP]; Spin-Neto, Rubens; Ferrisse, Túlio Morandin [UNESP] (Wiley, 2020)
Background: Odontogenic myxoma (OM) is a rare neoplasm, which originates from odontogenic ectomesenchyme. There is no study in the literature that analyses the best standards for OM diagnosis and how the treatment modalities may influence the recurrence rates. Objective: To evaluate the best standards for odontogenic myxoma (OM) diagnosis and treatment, and how these may influence the recurrence rates. Study design: Two independent researchers performed a systematic review in many databases. Fifty-two eligible studies were included for qualitative analysis. Bias analysis was conducted according to Oxford Centre for Evidence-Based Medicine. Results: A total of 1363 OM cases were reported on, and female gender with average age of 27 years is the most common patient profile. Conventional microscopic findings were observed in 93.43% of the reported cases. In 57.49% of the cases, multilocular radiographic appearance was present, followed by unilocular appearance (32.87%). Posterior mandible was the site with the major prevalence, while surgical resection was the most common treatment modality, followed by enucleation. Recurrence rates for both treatment modalities were approximately close (13.04% and 25.0%, respectively). Conclusion: The correct diagnosis of OM relies on the association of clinical, radiographic and microscopic findings. About imaging examinations, panoramic radiography and computed tomography are sufficient for the evaluation of OM. Recurrence rates were closely among the two most used surgery treatments. So according to some clinical-radiological aspects, conservative surgery may be preferred than aggressive surgery modalities.
Keywords: neoplasm; odontogenic myxoma; oral cavity; systematic review